Direct Observation of Strong Anomalous Hall Effect and Proximity‐Induced Ferromagnetic State in SrIrO3. Issue 14 (23rd February 2022) - Jaiswal, Arun Kumar; Wang, Di; Wollersen, Vanessa; Schneider, Rudolf; Tacon, Matthieu Le; Fuchs, Dirk
Abstract: The 5d iridium‐based transition metal oxides have gained broad interest because of their strong spin–orbit coupling, which favors new or exotic quantum electronic states. On the other hand, they rarely exhibit more mainstream orders like ferromagnetism due to generally weak electron–electron correlation strength. Here, a proximity‐induced ferromagnetic (FM) state with T C ≈ 100 K and strong magnetocrystalline anisotropy is shown in a SrIrO3 (SIO) heterostructure via interfacial charge transfer by using a ferromagnetic insulator in contact with SIO. Electrical transport allows to selectively probe the FM state of the SIO layer and the direct observation of a strong, intrinsic, and positive anomalous Hall effect (AHE). For T ≤ 20 K, the AHE displays unusually large coercive and saturation field, a fingerprint of a strong pseudospin–lattice coupling. A Hall angle, σxy AHE / σxx, larger by an order of magnitude than in typical 3d metals and an FM net moment of about 0.1 μB /Ir, is reported. This emphasizes how efficiently the nontrivial topological band properties of SIO can be manipulated by structural modifications and the exchange interaction with 3d TMOs. Abstract : A ferromagnetic state—rarely observed in 5d‐based transition metal oxides due to the generally weak electron–electron correlation—is induced in SrIrO3 by proximity to ferromagnetic insulating LaCoO3 . Electrical transport allows the ferromagnetism of SrIrO3 to be probed selectively, revealing a strong magnetocrystalline anisotropy and enabling the direct observation of a strong, intrinsic, and positive anomalous Hall effect.